Alcohol and other drug use, club drug dependence and treatment seeking among lesbian, gay and bisexual young people in Sydney. (1st November 2012) - Lea, Toby; Reynolds, Robert; de, John
Abstract Introduction and Aims Substance use and substance use problems are often more prevalent in same‐sex attracted young people (SSAY), yet little to date has been published about substance use and problems in this population in Australia. This paper aimed to characterise patterns of alcohol use, club drug use and dependence, injecting drug use and engagement with treatment services, comparing lesbians, gay men, bisexual women and bisexual men. Design and Methods A cross‐sectional, online survey was conducted with 572 SSAY in Sydney, aged 18 to 25 years. The Alcohol Use Disorders Identification Test—Consumption questions (AUDIT‐C) assessed hazardous alcohol use, and the Severity of Dependence Scale assessed club drug dependence. Results Seventy per cent of respondents had AUDIT‐C scores indicative of hazardous alcohol use, and 29% of respondents had used club drugs in the previous 6 months. Multivariate logistic regression showed that male respondents had a lower odds of hazardous alcohol use (adjusted odds ratio = 0.6, 95% confidence interval 0.4–0.9), but a higher odds of recent club drug use (adjusted odds ratio = 1.8, 95% confidence interval 1.2–2.7). Methamphetamine dependence was reported among half of respondents who reported use in the previous 6 months. Bisexual women were more likely than other respondents to have sought treatment for alcohol and other drug use, and overall treatment utilisation was low (6%). Discussion and Conclusions This study reports high rates of drinking and club drug use, and a possible underutilisation of alcohol and other drug treatment. The findings suggest that SSAY in Sydney may be at a high risk of alcohol‐ and drug‐related harm.